Management of Calcified Root Canal: A Case Report - Samrudhi Khatod1, Anuja Ikhar2 , Pradnya Nikhade3 , Arpan Jaiswal4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Calcification of root (calcific metamorphosis) is usually seen as defensive reaction of pulp totrauma. Intensity of trauma/hit, time span since trauma, pulp response to trauma are multiple factor decidingdegree of calcification. Calcification may be seen partially or entirely in root canal. Usually calcifiedtooth remain asymptomatic, but when tooth becomes symptomatic endodontic treatment need to be done.Treatment of calcified canal is challenge to dentist.Case report: A female patient reported to the department of conservative dentistry and endodontics at sharadpawar dental college with chief complain of pain in upper front region of jaw. On radiographic examinationcalcified root canal was associated with upper anterior teeth. Root canal treatment was planned for calcifiedtooth. Access opening was carried out using BR45. To achieve patency within canal file#8, 10 were used, butinitally patency could not be achieved due to calcified canal. With help of chelating agents 17% EDTA liquidand gel and small size K file #8,10 canal negotiation was carried out to achieve patency. Working lengh wasthen determined and canal was instrumented. Naocl, EDTA was used as intermittent irrigant. Final rinse wasdone using 2%CHX. Canal was obturated using cold lateral condensation technique followed by permanentrestoration. Entire procedure was carried out under magnification.Conclusion: Calcified canal treatment is bit tedious then routine endodontic procedure. But it can bemanaged if procedure is carried out under proper illumination, magnification, CBCT, understanding rootcanal anatomy, use of dye, modified access bur, files, chelating agent, irrigants and irrigation activationsystem.